Enhancing our understanding of vision in organizations: Toward an integration of leader and follower processes. (May 2016) - Berson, Yair; Waldman, David A.; Pearce, Craig L.
We put forth a theoretical model that considers alternative paths toward the formation of vision in collectives. We view vision as being shaped by a combination of hierarchical leader vision and shared leadership processes involving followers. As such, these paths balance leader- and follower-centric approaches to understand the formation of vision. A feature of our approach is that we emphasize some key processes and moderators; specifically, the role of the content of the vision of the leader, leader deontic fairness, and collective identification among members of the collective. We consider research implications including the measurement of shared vision, as well as practical implications pertaining to its relevance for such important outcomes as organizational learning.